Development and Application of Type-III Turbine Impedance Models Including DC Bus Dynamics - Jian Sun; Ignacio Vieto (IEEE Open Journal of Power Electronics, 2020)
Several small-signal impedance models have been reported for type-III wind turbines for use in impedance-based system stability studies. Common to these models is the assumption that the dc bus between the rotor- and stator-side converters is an ideal voltage source. Under this assumption, there is no dynamic coupling between the two converters and the turbine can be represented by the impedance of the stator-side converter in parallel with the impedance of the induction generator with the rotor-side converter behind it. The assumption is well justified above the second harmonic frequency but introduces considerable error at lower frequencies, especially within 20-30 Hz of the fundamental frequency in which dc bus voltage control is active and dc bus capacitor impedance is high. This paper presents the development and application of full-order sequence impedance models for type-III turbines that include dc bus dynamics. The new models also consider the coupled current responses created by each of the converters as well as their coupling across the dc bus. Inclusion of these additional dynamics leads to more accurate prediction of turbine impedance responses and turbine-grid system stability. A comparison with existing models is presented to show the utility and limitation of each model. A practical resonance problem is also presented to demonstrate the application.